Hubungan Kemampuan Awal dan Minat Terhadap Olahraga Prestasi Belajar Olahraga Mahasiswa FIK UNESA - Abdul Rachman St, ; Amrozi Khamidi, (Kepelatihan Olahraga, 2009)
The purpose of this research was to fmdne correlations between cognitive early and enthusiasm toward sport science, and achievement in sport science. The population of the study was the training students of FIK UNESA. There were 140 subjects sample chosen from the population. The Pearsons Product Moment and Multiple Correlation were applied to analyze the data. The results showed that: there was correlation between cognitive early and achievement in sport science; there was correlation between enthusiasm toward sport science; achievement in sport science can be predicted from cognitive early and enthusiasm toward sport science.